KEANEKARAGAMAN JENIS DAN MORFOLOGI Shorea spp. PADA KAWASAN WISATA AREAL GRANIT TAMAN NASIONAL BUKIT TIGAPULUH PROVINSI - Hasanah, Hafiz; Yoza, Defri; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Bukit Tigapuluh National Park has an ODTW (Tourist Attraction) that is attractive for tourists to visit and has a unique tourist attraction, namely the Granit area, a former Granit mining area. One of the dominant plant species in the Granit area's tourist attraction in Bukit Tigapuluh National Park is Shorea spp. This study aims to determine the diversity of species and morphology of Shorea spp. in the Granit tourist area in Bukit Tigapuluh National Park, Riau Province. This study used a purposive sampling method using a pathway system. The composition of tree species uses manuals and tree species records to obtain observations of species diversity, while morphological observations can be taken using cameras or data from the Bukit Tigapuluh National Park as supporting material. The results showed that the morphology of each Shorea spp. Species seen from the shape of the leaves and stems had differences. The diversity of meranti species (Shorea spp.) In the Granit area of Bukit Tigapuluh National Park (TNBT) was eight species with 67 individuals. The index value of species diversity (H ') in Granit Bukit Tigapuluh National Park (TNBT) is line 1, which is 1.81 in the medium category, and lane two is 0.89 with the low category, and lane 3 is 0.82 with the low category. Keywords: Morphology, national park, shorea spp.